Approach for transient interference detection based on straight line extraction for high‐frequency sky‐wave radar. Issue 9 (1st April 2017) - Luo, Zhongtao; Song, Tiecheng; He, Zishu; Hu, Jinfeng
Abstract : Transient interference cancellation is necessary for high‐frequency sky‐wave radar and usually requires accurate interference detection and localisation which is complicated due to the non‐uniform noise level caused by sea‐clutter mitigation in Doppler domain. A novel approach is proposed by converting the detection of interference into a problem of straight line extraction in the constructed fast‐ and slow‐time images. The line edges are detected by an edge detector, such as Canny method, followed by Hough transform. Then, each edge is classified as a rising, falling or false‐alarm edge based on multi‐threshold segmentation of image sub‐blocks. Experimental results demonstrate the effectiveness of the proposed approach.